EDUKASI KEPEMIMPINAN DAN PELATIHAN PBB GUNA MENINGKATKAN KINERJA ORGANISASI KEMAHASISWAAN DI POLTEKKES MAGELANG - Prapsetyo, Agung; Kiki Lestari (PPM Sdirjianbang Akademi Militer, 2023)
Leadership in an organization is a measure of the success of an organization in achieving its goals. To prepare leadership regeneration within the organization at the Magelang Health Polytechnic, a training program is needed for prospective student organization administrators. The training is the Basic Leadership Training (LDK) which aims to provide a comprehensive understanding of the basics of leadership to the new administrators of the Student Council (DEMA) and Student Association (HIMA) of the Magelang Health Polytechnic. With the goal they are expected to understand the basics of leadership and have a disciplined attitude and be responsible for carrying out their duties towards the organization so that organizational goals are achieved. The implementation method is with an education system about leaders and leadership, and is equipped with socialization of theory and practice of marching to improve discipline so that superior performance in organizations. The results of this community service activity are expected to be able to provide references, knowledge and knowledge, understand and foster a spirit of leadership and can be implemented in organizations both at DEMA and HIMA regarding the character of good and disciplined leadership in order to achieve organizational goals.